Strategic perspective codification of Iran martial arts federation - Soltanpour, S.; Hossein Razavi, S. M.; Sajjadi, S. N.; Honari, H. (Annals of Applied Sport Science, 2019)
Background. The current study aimed at codifying the strategic perspective of Iranian federation of martial arts sport. Objectives. The current study aimed at investigating the negative consequences of the use of social networks at the workplace from the viewpoint of the employees of the sports and youth departments. Methods. The current strategic study was conducted based on a combination of sequential explanatory methods. The statistical population of the study consisted of 138 individuals including the chairman, vice-chairman, and the secretary of the Iran Martial Arts Federation, the officials of the internal committees of the federation, the directors of provincial boards of martial arts, the directors of the styles (associations, committees, and groups), and the members of the Strategic Council of the Federation of which 43 individuals were selected to participate in the study using the Cochran formula. The data were collected through interviews, open and closed questionnaires, and Delphi method. The employed questionnaire had 27 items: seven in strengths, five in weaknesses, seven in opportunities, and six in threats. The validity of the research tool was assessed by 15 sport management experts and martial arts experts and its reliability was also confirmed by Cronbach's alpha coefficient for strengths (a = 796), weaknesses (a = 0.704), opportunities (a = 0.845), and threats (a = 0.774). To prioritize the strengths, weaknesses, opportunities, and threats, the Friedman test was used to determine the strategic position of the federation through weighing and the severity of each factor. In order to formulate strategies, SWOT analysis and pairwise comparison of ST, WO, SO, and WT were employed. Finally, the quantitative strategic planning matrix (QSPM) was used to prioritize strategies. Results. The strategic position of the Iran Martial Arts Federation in the SO region was codified. Conclusions. Based on the current study results, three SO, two WO, two ST, two WT, and nine strategies were presented to clarify the vision of the Iran Martial Arts Federation.